Analysis of workforce requirements based on WISN in radiology installation of RSU X - Diaz Farrasizdihar; Ermi Girsang; Sri Lestari Ramadhani Nasution (Universitas Muhammadiyah Yogyakarta, 2021)
The beginning of 2020 was shocked by the WHO's statement which mentioned Coronavirus-19 (COVID-19) as a pandemic. As many as 37420 confirmed cases of COVID-19 were reported by the Ministry of Health of the Republic of Indonesia until June 2020 and are growing every day. One of the supporting examinations to establish a diagnosis of COVID-19 is a radiological examination. It is undeniable that the increasing incidence of COVID-19 has caused the workload of health workers in hospitals is increase, including in radiology installations in hospital. The purpose of this study was to analyze the need of workforce according to the workload using the Workload indicators of staffing need (WISN) method in the radiology installation of the RSU X. This research uses quantitative and qualitative methods. The results showed that the workload of the workforce in the radiology installation at RSU X was in the optimum category. Based on calculations using the WISN method, it was found that the total number of workers needed at the radiology installation at the RSU X was 15 people and the workforce gap ratio was 1.00.